Strengthening Financial Literacy and Thrifty Character through Early Saving Education among Children at TK IT Baitul Izzah, Bengkulu City - Sylvia Noviriani; Linda Astuti; Levy Oktidarti; Yori Manis Tika; Shinta Wiji Rahayu; Heni Indriani; Hania Sumarni (JURNAL BESEMAH, 2026)
Financial literacy should be introduced from an early age to develop children’s understanding of the function of money, their ability to distinguish between needs and wants, and their habits of being thrifty and financially responsible. However, young children generally have limited knowledge of financial management; therefore, educational activities appropriate to their developmental characteristics are needed. This community service program aimed to strengthen financial literacy and foster thrifty character through early saving education among children at TK IT Baitul Izzah, Bengkulu City. The program employed a participatory and educational approach involving children, teachers, and parents in developing saving habits. The program was implemented through several stages, including initial needs identification, activity planning, interactive learning, saving practice simulations, evaluation, monitoring, and reflection. The educational materials were delivered using simple language, contextual examples, question-and-answer activities, and hands-on practices to facilitate children’s understanding of basic financial concepts. The results indicated positive improvements in children’s understanding and responses toward saving activities. Children began to recognize the benefits of setting aside a portion of their money, understand the basic distinction between needs and wants, and demonstrate greater motivation to develop regular saving habits. The saving simulation also helped children understand that achieving financial goals requires discipline, consistency, and a gradual process. The involvement of teachers and parents was identified as an important factor in sustaining saving habits beyond the program. These findings indicate that interactive and practice-based financial education can serve as an appropriate strategy for introducing financial literacy while fostering thriftiness, discipline, and responsibility among young children. The sustainability of the program requires consistent saving practices at school and at home, supported by continuous guidance and positive reinforcement from teachers and parents.